Numerical simulation of thermal water delivery in the human nasal cavity. (1st September 2018) - Covello, V.; Pipolo, C.; Saibene, A.; Felisati, G.; Quadrio, M.
Abstract: This work describes an extensive numerical investigation of thermal water delivery for the treatment of inflammatory disorders in the human nasal cavity. The numerical simulation of the multiphase air-droplets flow is based upon the Large Eddy Simulation (LES) technique, with droplets of thermal water described via a Lagrangian approach. Droplet deposition is studied for different sizes of water droplets, corresponding to two different thermal treatments, i.e. aerosol and inhalation. Numerical simulations are conducted on a patient-specific anatomy, employing two different grid sizes, under steady inspiration at two breathing intensities. The results are compared with published in vivo and in vitro data. The effectiveness of the various thermal treatments is then assessed qualitatively and quantitatively, by a detailed analysis of the deposition patterns of the droplets. Discretization effects on the deposition dynamics are addressed. The level of detail of the present work, together with the accuracy afforded by the LES approach, leads to an improved understanding of how the mixture of air-water droplets is distributed within the nose and the paranasal sinuses. Highlights: Inhalation deposits droplets in the nasal cavity more efficiently than aerosol. The paranasal sinuses receive a non-negligible amount of water droplets. A detailed analysis of deposition fraction is necessary to capture local effects. The deposition fraction depends upon the grid resolution.